2008
DOI: 10.1007/s15010-007-7162-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Acquired Pneumonia in HIV-Infected Inpatients in the Highly Active Antiretroviral Therapy Era

Abstract: The incidence of BCAP was high in HIV-infected inpatients observed in the present study mainly due to HIV infection itself, IVDU, alcohol abuse and smoking habit. A longer time to clinical stability was associated with advanced HIV infection and with S. pneumoniae etiology, while receipt of antiretroviral therapy was protective. Injection drug abuse treatment, alcohol abuse and smoking cessation programs, antiretroviral treatment adherence support and pneumococcal vaccination should be implemented to reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 23 publications
3
48
0
1
Order By: Relevance
“…Studies investigating aetiological agents in CAP have found pneumococci to be the cause of around 30-40% of cases of CAP among people with HIV infection [14,41]. PPV-23 covers $ 70% of the serotypes causing CAP [42] and $ 90% of serotypes causing IPD [6,14,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating aetiological agents in CAP have found pneumococci to be the cause of around 30-40% of cases of CAP among people with HIV infection [14,41]. PPV-23 covers $ 70% of the serotypes causing CAP [42] and $ 90% of serotypes causing IPD [6,14,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary infections Community-acquired pneumonia It is well recognised that smoking is an independent and eminently preventable risk factor for the development of CAP in both HIV-infected and -uninfected individuals [13,[93][94][95][96][97][98][99]. In HIV-infected patients, the increased risk for CAP, which is evident at all levels of immunosuppression, is estimated to be between two-and five-fold, increasing as the CD4 cell count declines [13,100].…”
Section: Clinical Consequences Of the Cumulative Effects Of Hiv Infecmentioning
confidence: 99%
“…Similar to that in the general population, Streptococcus pneumoniae and Haemophilus species are the most frequently identified causes of community-acquired bacterial pneumonia (Hirschtick et al, 1995;Madeddu et al, 2008;Schneider, 1999). Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa account for most of the remainder of cases (Afessa & Green, 2000;Baron & Hollander, 1993;Madeddu et al, 2008). Risk factors for S. aureus include recent viral or influenza infection and use of injection drugs.…”
Section: Bacterial Infectionsmentioning
confidence: 98%
“…Other risk factors are a low socioeconomic, alcohol abuse status, comorbidities (including cardiovascular, renal disease malnutrition, and hepatic cirrhosis), low CD4 cell counts (<200 cells/ml), uncontrolled HIV replication and not receiving ART (Madeddu et al, 2010). Similar to that in the general population, Streptococcus pneumoniae and Haemophilus species are the most frequently identified causes of community-acquired bacterial pneumonia (Hirschtick et al, 1995;Madeddu et al, 2008;Schneider, 1999). Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa account for most of the remainder of cases (Afessa & Green, 2000;Baron & Hollander, 1993;Madeddu et al, 2008).…”
Section: Bacterial Infectionsmentioning
confidence: 99%